EFEKTIVITAS KEBIJAKAN SEKOLAH TERHADAP KINERJA GURU SMP PGRI 01 KARANGPLOSO MASA PANDEMI COVID-19 - Moh. Askiyanto; Muhammad Yusi Kamhar (Unitri Press, 2021)
The purpose of this study was to evaluate the effectiveness of school policies in order to assess the level of teacher performance at SMP PGRI 01 Karangploso during the pandemic, where teachers are required to conduct effective learning activities even during the pandemic, which necessitates online learning activities. Additionally, there are assumptions that the use of online learning was considered ineffective because of a lack of school preparation and a lack of student readiness, as well as a lack of facilities to support online learning activities and a lack of effective regulations defining appropriate policies for the learning and pursuit process. The quantitative descriptive method was used in this study, and data were gathered through observations and in-depth interviews with various teachers and policymakers at schools. According to the findings of this study, the efficacy of school policies was classified as fairly effective, with an average score of 55,15. As a result, the policies established in schools must undergo revision by the parties involved. They must collaborate and assist one another. Among them are teachers as practitioners of learning, students as learning ob jects, school administration as suppliers of learning services, and parents as those responsible for providing online learning support facilities.